Peran Katekese dalam Mempersiapkan Perkawinan Gereja Katolik - Elisabeth Yecilda Woga; Fransiska Masandai Jawan; Patrisia Rera Bato (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the role of catechesis in preparing couples for marriage in the Catholic Church comprehensively, encompassing theological, spiritual, mental, and emotional dimensions. The background of this study is based on the phenomenon that some couples still enter into marriage without adequate faith preparation, thus implicating a low understanding of the meaning of the sacrament of marriage as a holy and inseparable life partnership. The research method used is a quantitative approach with a Likert-scale questionnaire as the data collection technique. The research instrument was compiled based on three main indicators, namely understanding the teachings of the sacrament, family function, and church life. Data were analyzed descriptively to measure respondents' perceptions of the effectiveness of catechesis in preparing for Catholic marriage. The results showed that the role of catechesis obtained a high average score of 37.34, with 83.87% of respondents in the strongly agree category. This indicates that catechesis plays a significant role in shaping the spiritual and psychological readiness of prospective couples. The implications of this research confirm that catechesis does not only function as a process of teaching faith, but also as an integral pastoral tool in building Catholic families based on love, loyalty, and Christian responsibility, and contributes to strengthening the faith of the church community. .